PENGARUH PEREBUSAN SAYUR BAYAM MERAH (Amaranthacea gangeticus) TERHADAP KANDUNGAN NITRIT (NO₂⁻) DENGAN BERBAGAI VARIASI WAKTU - Nasution, Sri Bulan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2018)
The red spinach is a complementary vegetable dish that has a characteristic feature that the stems and leavesof red. Chemical substances that can be found are protein, fat, carbohydrates, potassium, iron, amaranthin,routine and purin, and vitamin A, B and C. In general, people already know that spinach vegetable stew canheated, but many do notknow how much influence a change in the nitrite content of boiling red spinach witha variety of time. The purpose of this study was to analysis effect of boiling red spinach to the nitrite (NO₂⁻)content with variety of time for 0 hours, 3 hours, and 5 hours. The maximum limit allowed nitrite levels inaccordance ADI (Total Daily Intake) established by WHO is 8 mg Nitrite per 60 kg body weight orequivalent to 0,133 mg Nitrite/kg body weight. Nitrite content in a vegetable stew ofred spinach wasdetermined using quantitative methods that measuring the value of nitrite contentin the boiled red spinachwith variety of time for 0 hours, 3 hours, and 5 hours with diazo method and using a spectrophotometer.From the results of the research it was obtained with variations in time 0 hours, 3 hours, and 5 hours were5,14 mg/kg; 10,25 mg/kg; dan 13,05 mg/kg. During stroge 0 hours to 3 hours increased 100% and for 3hours to 5 hours had 30%. Storage red spinach vegetable stewfor 5 hours was seaved for consumption forthe people with its weight body 60 kg’s in the result of boiled vegetable red spinach according to totalamount ±611,4 grams of the result according with maximum limit of Acceptable Daily Intake (ADI)established by WHO. By knowing the nitrite content in a vegetable stew of red spinach is expected toconsumers to immediately process the red spinach after purchase and consume immediately after cookingand not for too long vegetable red spinach store in the refrigerator.